An Experience in Managing an open Fracture Shaft of the Femur Due to a Gunshot with Intramedullary Interlocking Nailing - Fayyaz Ahmed Orfi; Hussain, Shafqat; Shafaan Orfi; Ali Arslan Munir; Sumbal Rana; Nida Maryam (Pakistan Armed Forces Medical Journal, 2023)
Objective: To evaluate functional outcomes and complications in gunshot femur shaft fractures treated with intramedullary nailing primarily. Study Design: Prospective longitudinal studyPlace and Duration of Study: Department of Orthopaedic Combined Military Hospital, Nowshera, Combined Military Hospital Sialkot, Combined Military Hospital, Rawalpindi Pakistan, from Jan 2016 to Dec 2021.Methodology: A total number of 53 cases of open fracture of the femur shaft due to gunshot were included in the study. After initial wound debridement, an X-ray was taken, and fractures were classified according to the Gustilo–Anderson classification. All fractures were fixed with titanium I/M I/L Nail in static mode by the same orthopaedic surgeon. Rehabilitation was instituted immediately after the operation, and the outcome was assessed in regards to infection, range of motion at the knee, full weight bearing and radiological union achieved.Results: Thirty-four (64.15%) patients had Type-1 fractures of the femur shaft, and 19(35.8%) patients had Type-2 fractures. Fracture union was observed in 47(88.67%) patients after three months and 6(11.32%) over the next five months. Complications were wound infections 5(9.44%), leg length discrepancy 4(7.53%), and non-union 2(3.77%) at six months. In these two cases, bone grafting was done, and union was achieved.Conclusion: Primary intramedullary (IM) is the preferred mode of treatment of Type 1 and 2 shafts of femur fractures if early good debridement is done. It avoids secondary procedures, has fewer complications and helps in early mobilization.